PENGARUH EFEKTIVITAS SUPERVISIOR TERHADAP PEMBERDAYAAN KARYAWAN LEMBAGA KEUANGAN MIKRO DI KOTA BANDUNG - Nenny Rinawati; Retno Resawati (STMIK Mardira Indonesia, Bandung, 2019)
This research was conducted at a micro finance company in the city of Bandung which focuses on the effectiveness of supervisors that influence employee empowerment. Quantitative research methods with a cross-sectional survey approach. The sampling technique uses simple random sampling on 100 employees. Data processing analysis techniques using simple regression analysis. The results of the study support the initial assumption that there is a influence of the effectiveness of supervisors on employee empowerment at financial institutions in the city of Bandung. Keywords: effectiveness, supervisior, employee empowerment.